STRATEGI PEMERINTAH DAERAH TERHADAP PROGRAM VAKSINASI COVID-19 KHUSUS LANSIA DI KELURAHAN SIALANG MUNGGU KOTA PEKANBARU TAHUN 2021-2022 - Virani, Jenika; Harirah, Zulfa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research aims to determine the regional government's strategy in the Covid-19 vaccination program especially for the elderly in Sialang Munggu Village, Tuah Madani District, Pekanbaru City. And to find out the inhibiting factors in implementing the program. The theory used in this research is strategy theory according to Siagian, namely accountability, deadlines and resources. The type of research used is qualitative. Meanwhile, the research approach used is descriptive. Data was collected by the author using interview and documentation techniques. The data used is primary data obtained from research informants and further supported by secondary data obtained from various government agencies related to this research. The results of the research show that the strategy carried out by Sialang Munggu Village for several Covid 19 vaccination programs specifically for the elderly is in the form of setting targets so as to ensure that the targets or goals are achieved with accountability. The second strategy provides a deadline for the implementation of each program that will be carried out ( Deadlines) and the third strategy ensures that the appropriate resources are used, namely in the form of a budget, human resources appropriate to the field and finally adjusting the infrastructure or facilities that will be used to make program implementation easier (Resource requirements). All strategies that have been carried out are included in the not optimal category. This is indicated by the achievement of vaccination for the elderly in Sialang Munggu Village only at 27.21% of the specified target of 85%. Keywords: Strategy, Vaccination of the Elderly, Sialang Munggu Village